Resolvin D3 multi-level proresolving actions are host protective during infection. (November 2018) - Norris, Paul C.; Arnardottir, Hildur; Sanger, Julia M.; Fichtner, David; Keyes, Gregory S.; Serhan, Charles N.
Abstract: Resolution of infection and inflammation is governed by innate immune cells. The resolvin family of n-3 mediators produced by resolving exudates stimulates clearance of neutrophils and attenuates pro-inflammatory signals. Using metabololipidomics, endogenous resolvin D3 (RvD3) was identified in self-resolving exudates during active E. coli infection. Through a new, independent synthetic route for RvD3, we matched endogenous and synthetic RvD3 and determined that RvD3 (ng doses) potently reduced the resolution interval ( Ri ) by 4.5 h during E. coli peritonitis after administration at peak inflammation ( T max =12 h) and increased leukocyte phagocytosis of E. coli and neutrophils as well as reduced proinflammatory cytokines, chemokines, MMP-2 and MMP-9. At pM-nM concentrations, RvD3 also enhanced human macrophage efferocytosis and bacterial phagocytosis, increased neutrophil bacterial phagocytosis and intracellular ROS generation, and reduced human platelet-PMN aggregation. These results provide additional evidence for potent RvD3 immunoresolvent actions in host defense, host protection and antimicrobial defense.